Flow-Induced Shear Stress Combined with Microtopography Inhibits the Differentiation of Neuro-2a Cells - Eleftheria Babaliari; Paraskevi Kavatzikidou; Dionysios Xydias; Sotiris Psilodimitrakopoulos; Anthi Ranella; Emmanuel Stratakis (Micromachines)
Considering that neurological injuries cannot typically self-recover, there is a need to develop new methods to study neuronal outgrowth in a controllable manner in vitro. In this study, a precise flow-controlled microfluidic system featuring custom-designed chambers that integrate laser-microstructured polyethylene terephthalate (PET) substrates comprising microgrooves (MGs) was developed to investigate the combined effect of shear stress and topography on Neuro-2a (N2a) cells’ behavior. The MGs were positioned parallel to the flow direction and the response of N2a cells was evaluated in terms of growth and differentiation. Our results demonstrate that flow-induced shear stress could inhibit the differentiation of N2a cells. This microfluidic system could potentially be used as a new model system to study the impact of shear stress on cell differentiation.